The effect of individual characteristics and academic integrity policies on academic dishonesty practices / Mohd Sobre Ismail, Amirrul Muhminin Darussamin and Muraddin Purag - Ismail, Mohd Sobre; Darussamin, Amirrul Muhminin; Purag, Muraddin (Universiti Teknologi MARA, Sabah, 2017)
Understanding academic dishonesty nowadays is important as the trend shows that academic cheating is recurring and somehow has become an accepted practice among students. Previous studies suggested that individual characteristics would be able to curb this problem. The same goes to academic integrity policies such as enforcement of stringent academic regulation on cheating practices would help to mitigate this problem. However, some studies revealed that individual characteristics and academic integrity policies would not be able to reduce cheating behaviour. Due to this inconsistency, the current study aims to investigate the effect of individual characteristics and academic integrity policies on cheating behaviour among students. A survey was utilized for the collection of data in which undergraduates students in a Malaysian university were used as sample. Self-esteem and mastery level of an individual were used as proxy for individual characteristic. The findings from this study showed that individual characteristics and academic integrity policies have significant effect in mitigating academic dishonesty.